Quantification of leaching of bases in soils using lysimeters under two hydric regimes - Casanova, O. N.; Ferrando, M. G. (Agrociencia Uruguay, 2003)
Under the Uruguayan precipitation regime, cations leaching with drainage water could result in increasing soil desaturation, specially in low CEC soils. Ultimately, this process could lead to cations enrichment of underground water, increased soil acidity and loss of soil fertility. During three years, undisturbed cores of five different Uruguayans soils were evaluated in lysimeters. Treatments were 1) natural rain, and 2) 150 mm of irrigation in addition to natural rain, after crop planting, with four replications. Annual crop rotation was winter crop (barley) and summer fallow. All lysimeters received 100kg ha-1 of N and P applied at planting. After each rainfall event, water drainage load and Ca, Mg, K and Na concentration in the drainage water were measured . Differences were found in total cations leaching, related with soil type, parent material and hydric regime. The total three years loss of bases varied between 288 and 617kg ha-1. Calcium (55-351kg ha-1) and Sodium (11-314kg ha-1), were the most contrasting elements, and this difference was related to soil type. At least for the period of study, the amount of cations leached from soil were not enough to significantly affect their exchangeable amount in soil.